A Review and Summary of Patients with Symptomatic Postoperative Discal Pseudocysts of the Lumbar Spine - Zhenlu Cao; Yanan Cong; Chuqiang Yin; Yuelei Wang; Zhichao Wang; XiaoWei Liu; Ting Wang (Orthopaedic Surgery, 2023)
Objective Postoperative discal pseudocyst (PDP) is a rare complication after discectomy. This study aimed to summarize the characteristics, pathological mechanisms and management of PDPs. Methods Nine patients with PDP who received surgical treatment at our institution from January 2014 to December 2021 were retrospectively reviewed. A systematic review of the literature on PDP was performed. The demographic data, clinical and imaging features, surgical options and patient prognosis were analyzed. Results Among the nine patients treated at our center, seven were male and two were female. The mean patient age (± standard deviation) at the time of surgery was 28.3 ± 5.7 years (range 18–37 years). The first operation performed on seven patients was percutaneous endoscopic transforaminal discectomy (PETD) and two patients underwent microdiscectomy. The time to conservative treatment before surgical intervention was 20 ± 9.2 days. In three cases, the disc cysts were located in L4/5 and in six cases the lesions were located in L5/S1. Intervertebral disc cyst interventions included foraminal scope (three cases), open discectomy (three cases), conservative treatment with a quadrant channel (one case) and CT‐guided puncture (one case). All patients fully recovered after surgery and the mean follow‐up time was 3.5 ± 2.1 years. A literature review identified 14 relevant articles that reported 43 PDP cases of PDP. Conclusion PDP occurs in Asian males with mild intervertebral disc degeneration and occurs 1 month after discectomy. Treatment should be based on specific patient scenarios. Conservative treatment is necessary and surgery should be performed with caution.